2021
DOI: 10.1186/s12911-021-01480-3
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of asymptomatic carotid atherosclerosis with electronic health records: a comparative study of six machine learning models

Abstract: Background Screening carotid B-mode ultrasonography is a frequently used method to detect subjects with carotid atherosclerosis (CAS). Due to the asymptomatic progression of most CAS patients, early identification is challenging for clinicians, and it may trigger ischemic stroke. Recently, machine learning has shown a strong ability to classify data and a potential for prediction in the medical field. The combined use of machine learning and the electronic health records of patients could provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Recently, machine learning methods have been a powerful tool for precision medicine in stroke [17,[21][22][23][24]26]. Meanwhile, these methods are also applied to different data formats [25,[34][35][36]. Nevertheless, applications of machine learning for TOAST subtypes classification is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning methods have been a powerful tool for precision medicine in stroke [17,[21][22][23][24]26]. Meanwhile, these methods are also applied to different data formats [25,[34][35][36]. Nevertheless, applications of machine learning for TOAST subtypes classification is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…A certain study by Fan et al [79] shows the comparison of six different ML-based models that are used in the diagnosis or prediction of Carotid Atherosclerosis by combining electronic health record data, like ultrasonography [80] , with ML algorithms like Logistic Regression, Random Forest, Decision Trees, etc. The analysis revealed that Logistic Regression showed the highest predictive ability, which was also verified by tenfold cross-validation, whereas decision trees showed the poorest predictive performance.…”
Section: Applications In the Present Scenariosmentioning
confidence: 99%
“…Patient data analyzed using these algorithms has shown efficient detection and diagnosis, better response to healthcare services, accompanied by the increase in clinical efficiency and resource reallocation (especially in the case of predictive algorithms) [15] , [16] . Very recently, combinations of ML-based algorithms with deep learning and ensemble systems have been successfully implemented in the diagnosis and detection of various traditional diseases like cancer and Alzheimer's disease [63] , [72] , [75] , [79] , [82] , [83] and even in the case of Covid-19 [50] , [86] , [89] , which has been ravaging the world. Some models have also been used to study pathogenesis and other aspects of cellular biology [36] .…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%
“…Machine learning (ML) has been used and has shown an acceptable performance in predicting the risk of diseases [ 10 , 11 , 12 ]. Therefore, in the current study, we used simple clinical data obtained by an ML model to predict LAAV and aim to examine the feature importance of the ML model to understand its mechanism.…”
Section: Introductionmentioning
confidence: 99%